Proposed Noatak National Arctic Range, Alaska : final environmental statement - United States. Department of the Interior. Alaska Planning Group. ([Washington] : Alaska Planning Group, U.S. Dept. of the Interior, 1974)
Cover title: Noatak National Arctic Range. Mode of access: Internet.